An enhanced feedforward flux weakening control for high‐speed permanent magnet machine drive applications. Issue 13 (16th August 2021) - Lang, Xiaoyu; Yang, Tao; Li, Chen; Yeoh, Seang Shen; Bozhko, Serhiy; Wheeler, Patrick
Abstract: Permanent magnet machines have been used in the high‐speed drive applications due to their high‐efficiency, high‐power‐density, and wide‐speed range characteristics. However, control of such high‐speed permanent magnet machines machine is always challenging and proper flux‐weakening controller design is essential to achieve high performance of these machines. In this paper, an improved feedforward flux‐weakening control scheme for interior permanent magnet synchronous machine (IPMSM) drives are proposed. The proposed method identifies optimal d ‐axis and q ‐axis currents under different operation regions using maximum‐torque‐per‐ampere curve, voltage limit, and current limit curves with a fast Newton–Raphson algorithm. To ensure the optimal performance of the control mechanism, effects of inductance variations due to the magnetic saturation are considered and an innovative high‐frequency staircase voltage injection method is used to identify the q ‐axis inductance. The experimental results show that compared with other existing flux‐weakening methods, the proposed technique can improve the DC‐link voltage utilisation without the need to tune any controller gains and can fully utilise maximum available torque with desirable transient performance.